How to choose a grad school [graduate studies]. - Karlin, S.
This paper provides some useful tips when choosing a graduate program. While some consider curriculum flexibility when making their choice, others, especially those with established careers, consider the availability of distance or part-time learning and the presence of course materials. Still, there are those who choose graduate programs that would allow them to pursue research work or programs with available engineering scholarships. It is also important to visit the campuses where the graduate programs are being offered to get a firsthand assessment of the culture, student population, faculty, and research facilities.
Keywords: Curriculum flexibility; Engineering scholarships; Graduate program; Graduate school; Students training